Applying the Common Sense Model to predicting quality of life in alopecia areata: The role of illness perceptions and coping strategies. (September 2019) - Willemse, Heidi; van der Doef, Margot; van Middendorp, Henriët
Applying the Common Sense Model, this cross-sectional study examines associations between illness perceptions and quality of life and the mediating role of coping in 243 adults with alopecia areata, a chronic dermatological condition. At least some QoL impairment was reported by 84 percent of participants, with 31 percent reporting very to extremely large impairment. Stronger perceptions of consequences, emotional representations, identity, and lower attribution to chance were related to more impairment, with avoidant coping acting as (partial) mediator. Illness perceptions and avoidant coping seem to play an important role in QoL and are relevant intervention targets in alopecia areata.